Social Influences on Influenza Vaccination Decision Among Senior Citizens in Taiwan, South Korea, and Switzerland - Schulz, Peter Johannes; Wu, Yi-Chen; An, Soontae; Chen, Fu-Li (Frontiers in Communication, 2019)
Background: Although the vaccination against influenza has been found to be an impactful and cost-effective protection against the disease, coverage is incomplete. This draws attention to the factors of people’s flu vaccination decisions. The article contributes to understanding the effect of social factors on vaccination behavior. Social factors comprise the ways people may be affected by their peers and the mass media or by healthcare providers and health institutions. Method: Samples of some 200 senior citizens were interviewed by write-in questionnaire in Taiwan, South Korea and the Swiss canton Ticino. Results: Encouragement by the family physician and a combination of the frequency of contact with vaccination subjects in interpersonal and traditional mass communication and perceived concern with vaccination there increased vaccination rates in the two Asian countries, and model behavior and experience strongly affected vaccination in South Korea, all in bivariate analyses. Multivariate regression in Taiwan and Korea loses the impact of mass media. Perceived concern in sources showed complete mediation by frequency of interpersonal communication in Taiwan and partial mediation in Korea. Conclusion: There is indeed a relationship between social factors and individual vaccination behavior, which, however, is far from being pervasive. There’s hardly any result with direct relevance for the hypotheses that shows up in all three countries, and a meaningful and clear pattern in the differences between the Swiss sample on the one hand and the two Asian countries emerges.